PENGARUH LOYALITAS TERHADAP TENAGA PENJUAL, DAN LOYALITAS TERHADAP TOKO PADA PERILAKU WORD OF MOUTH - Mulyanto, Kukuh (STIE Totalwin Semarang, 2012)
The purpose of this research was to examine empirically the correlation between loyalty to salesperson and loyalty to the store. The subjects of this research were 98 customer of Distro, taken from population using purposive sampling technique. Data analyze instrument used by the writer is SPSS 17. Data analyze result shows that the research model has well appropriateness and all hypothesis of the study are able to be evidenced. Summary said that loyalty to salesperson, and loyalty to the store are positively effected to word of mouth behavior. Based on the result of the study, managerial implication given to the company is suggestion or input to management to give more concern at the loyalty to the store, as it is the most dominant factor effected to word of mouth. Â Keywords: word of mouth, loyalty to salesperson, loyalty to the store